The royal ranger - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2014)
The once mischievous and spirited Ranger's Apprentice, Will, is now a grim, humorless grown man who has lost his beloved wife. The Rangers, though they still exist, lack energy and leadership. The unexpected arrival of headstrong Maddie, the daughter of Horace and Evanlyn, promises new energy. But can this troublesome girl who has no interest in her royal status become a Ranger? Now, Will must prove his mettle by taking on an apprentice of his own.